Involvement of Different Nerve Branches in Trigeminal Neuralgia on Right and Left Sides- A Retrospective Study - K. Caroline Sunitha; Arvind Muthukrishnan; Ramesh R (International Journal of Pharma and Bio Sciences, 2022)
One of the most common symptoms in the orofacial region is pain. Trigeminal neuralgia is characterized by pain affecting the trigeminal nerve and its related areas of distribution and is known to have significant impact on the quality of life. Misdiagnosis of trigeminal neuralgia has been reported by dentists in several previous studies in the literature. With this rationale, the aim of the present study is to determine the most commonly involved nerve branch and the side affected in trigeminal neuralgia patients. The present retrospective study involved 72 patients diagnosed with trigeminal neuralgia who reported from October 2013 to October 2014. Data regarding the age of onset, gender, side of involvement was analyzed from their clinical records. Out of the 72 patients, males were 42(58.3%) and females were 30(41.7%). In our study, a total of 56 % (i.e., 40) patients showed involvement on the right and 44% (i.e., 32) (i.e, 32) patients on the left side of the face. In this retrospective study, ophthalmic branch (V1) was affected only in 3 patients. Mandibular nerve (V3) alone was involved in 24 patients. Involvement of all the three divisions V1, V2 and V3 was seen in 16(22.3%) of patients. Clinical similarities of trigeminal neuralgia that have an impact on different populations were demonstrated in this study. Detailed history and proper identification of involved nerve branch play an important role in the diagnostic accuracy and treatment satisfaction. Most involved branch in our study was the mandibular (V3) branch and the most affected side was the right side. Correlation of systemic factors with trigeminal neuralgia can be attempted in future research.